Over-expression of MAGED4B increases cell migration and growth in oral squamous cell carcinoma and is associated with poor disease outcome - Chong, Chan Eng; Lim, Kue Peng; Gan, Chai Phei; Marsh, Christina A.; Zain, R.B.; Abraham, Mannil Thomas; Prime, Stephen S.; Teo, Soo-Hwang; Gutkind, J.S.; Patel, Vyomesh; Cheong, Sok Ching (2012)
MAGE proteins have been shown to be good targets for cancer immunotherapy. We demonstrate that MAGED4B is over-expressed in more than 50 of Oral Squamous Cell Carcinoma (OSCC) tissues and the expression of MAGED4B is associated with lymph node metastasis and poor disease specific survival. OSCC cell lines that over-express MAGED4B promote migration in vitro, exhibit an increase in cell growth both in vitro and in vivo, and are more resistant to apoptosis compared to control cells. Our data suggest that MAGED4B over-expression is a driver in oral carcinogenesis and argues strongly that this protein may represent a potential therapeutic target in OSCC.